2007
DOI: 10.1002/anie.200700443
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Switches Flipped by Oxygen

Abstract: Singlet oxygen fuels anthracenes and forces an axial rotation of aryl substituents during the oxidation. The molecular switch can be synthesized in only one step from commercially available starting materials. Thermal cleavage of the resulting endoperoxides proceeds quantitatively and affords a simple 180° switch with oxygen as the only waste product. The initial trans state is attained by heating, and repetitive cycles are possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 55 publications
2
56
0
Order By: Relevance
“…in 13 C NMR analysis (Supplementary Fig. S9a)2021. The 9,10-endoperoxide was also formed by 4 under the same experimental conditions (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…in 13 C NMR analysis (Supplementary Fig. S9a)2021. The 9,10-endoperoxide was also formed by 4 under the same experimental conditions (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 73%
“…3a) peaks of the anthracene chromophore of 4 in solution had completely disappeared after just 2 h (Supplementary Figs S5 and S6). This could be attributed to conversion of the anthracene unit into 9,10-endoperoxides upon irradiation20. The 1 H resonance characteristics of the parent anthracene protons exhibited significant changes upon irradiation (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Zehm, Fudickar, and Linker [41] set up molecular rotary switches of bisarylanthracenes flipped by covalent binding [42], then release of oxygen (Fig. 8b,c).…”
Section: Molecular Switchesmentioning
confidence: 99%
“…[ 7 ] The predominant mechanism for this molecule involves activation of O 2 molecules by the initially-formed excited state; this either generates singlet O 2 species or a superoxide O 2 − which then adds back across appropriate carbon centres in TIPS-pentacene to produce an endoperoxide (EPO), which is seen as the main product by NMR. [ 7 ] Recent studies using chemically generated [ 8,9 ] singlet O 2 have further demonstrated that the superoxide route is the most favoured of the two for TIPS-pentacene, contributing around 90% to the overall rate of EPO formation. Electron transfer rates from excited-state pentacenes are also observed to be fast and solvent-dependent.…”
Section: Concentration-and Solvent-dependent Photochemical Instabilitmentioning
confidence: 99%